The health of the federal public servant in a university hospital: an analysis of absences from work recorded in a medical expert unit (Research, Society and Development, 2022)
The objective of this research was to evaluate the epidemiological profile and the predominant pathologies that lead health professionals from a federal university to leave work due to illness. This is a cross-sectional, retrospective study, whose target population is health professionals who work at a university hospital, at a federal university, and who left work due to illness in 2019. The results found showed that most professionals at the university hospital who became ill were female (N= 92, 86.80%), occupied the position of nursing assistant (N= 47, 44.30%), with a median leave of absence of 23 (IIQ; 11-90 ) days. The main causes of illness at health campus were musculoskeletal and connective tissue diseases (N=109, 22.15%) and mental and behavioral disorders (N=72, 14.63%). With this study, it was verified that a more in-depth assessment of mental health and ergonomic conditions to which these workers are submitted is important.